2010
DOI: 10.1093/nar/gkq961
|View full text |Cite
|
Sign up to set email alerts
|

Improved specificity of gene silencing by siRNAs containing unlocked nucleobase analogs

Abstract: siRNAs confer sequence specific and robust silencing of mRNA. By virtue of these properties, siRNAs have become therapeutic candidates for disease intervention. However, their use as therapeutic agents can be hampered by unintended off-target effects by either or both strands of the siRNA duplex. We report here that unlocked nucleobase analogs (UNAs) confer desirable properties to siRNAs. Addition of a single UNA at the 5′-terminus of the passenger strand blocks participation of the passenger strand in RISC-me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
79
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(82 citation statements)
references
References 25 publications
3
79
0
Order By: Relevance
“…In addition, it could be very interesting combining our approach of siRNA passenger strand modification to generate thermodynamically stabilized siRNA duplexes with guide strand modifications. Very interesting combinations could be siRNA guide strand modifications in the seed region, which have been described to cause reduced siRNA off-target activity, for example, 29-O-methyl nucleotides (Jackson et al 2006a) or UNA nucleotides (Bramsen et al 2010;Laursen et al 2010;Vaish et al 2010). Since siRNAs are being used as drugs our siRNA selection parameters may also have an impact on siRNA-based therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it could be very interesting combining our approach of siRNA passenger strand modification to generate thermodynamically stabilized siRNA duplexes with guide strand modifications. Very interesting combinations could be siRNA guide strand modifications in the seed region, which have been described to cause reduced siRNA off-target activity, for example, 29-O-methyl nucleotides (Jackson et al 2006a) or UNA nucleotides (Bramsen et al 2010;Laursen et al 2010;Vaish et al 2010). Since siRNAs are being used as drugs our siRNA selection parameters may also have an impact on siRNA-based therapy.…”
Section: Discussionmentioning
confidence: 99%
“…One of the major concerns is off-target gene-expression effects. A variety of modifications of siRNA chemistry or structure have been introduced to minimize the off-target effect (Martinez et al, 2002;Chiu and Rana, 2003;Kim et al, 2004;Siolas et al, 2004;Judge et al, 2005;Sun et al, 2008;Bramsen et al, 2009;Vaish et al, 2011). It has been recently reported that modifying siRNAs with unlocked nucleobase analog could markedly reduce the off-target effects (Vaish et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Two potential mechanisms resulting in off-target silencing have been elucidated (Vaish et al, 2011). One is accidental incorporation of passenger strand that could guide RISC to cleave the sequence complementary to its normal target.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vivo nuclease resistance of this structure is enhanced [42]. In contrast to LNA, derivatives of RNA without C2′-C3′ sugar bonds (unlocked nucleic acid-UNA) destabilize a sequence structure [43]. Substitution of pentose with hexose monosaccharides, such as cyclohexenyl, anitrol, and arabinose, was applied to develop CeNA, ANA, and 2′-F-ANA [44], subsequently resulting in enhanced stability of siRNA in vivo [45].…”
Section: Stabilizing the Sirna Deliverymentioning
confidence: 99%